Estrategias de recaudación en la renta de primera categoría para un control tributario, en el distrito de Chachapoyas - Amazonas, periodo 2020 - Ruiz Vásquez, Daniel Mauricio (2022)
The present research work called "Collection strategies in the First Category Income for a tax control, in the district of Chachapoyas - Amazonas, period 2020", was developed with the general objective of Proposing alternatives and strategies to complement the Tax Control in the improvement of the collection of the First Category Income Tax for the Leasing of Properties in the District of Chachapoyas, and with the specific objectives of determining the causes that originate the low collection of the First Category Income Tax for the Leasing of Properties in the District of Chachapoyas, Establish alternatives in tax and administrative regulations, which allow improving the collection of the First Category Income Tax; Therefore, there was a population sample of 384 owners who lease their properties in the District of Chachapoyas; Several techniques were used, including the Survey, and the Questionnaire as an instrument to collect information. It was determined that the results obtained meet the proposed goals for the collection of the First Category Income Tax, therefore the implementation of new strategies that contribute to the improvement of the collection levels is necessary; Likewise, the causes by which taxpayers evade their tax responsibilities were determined, which are the lack of tax culture, the high tax rates of the Tax, the distrust of SUNAT or the authorities in charge of the administration of Taxes, and the dissatisfaction. to the public services they receive.